Impact of the use of ICT on the levels of reading comprehension in students of the 5th JM grade of the Nicolás Gómez Dávila School - Romero Henao, Edna Viviana; Melo Fontecha, Sara (Rastros Rostros, 2023)
The research process proposed in this document provided a description about the impact of using the digital tools that have managed to engage the student and in turn, it allowed to establish whether, in addition to raising motivational levels, it could influence the development of skills related to reading comprehension processes. For this reason, the general objective is: "To describe the impact of the using ICT on the levels of reading comprehension in students of 5° grade JM in the Nicolás Gómez Dávila School". For this purpose, it was necessary to delve into the following categories of analysis: Reading Comprehension, ICT tools and family support in reading comprehension processes. The research approach was qualitative and the research design was based on the premises of research & action. In order to achieve the research objective, the following instruments validated by an expert were applied: a survey to parents, three entrance tests and three exit tests of reading comprehension to 15 students in 5° grade JM. This allowed us to generate some recommendations aimed at strengthening reading comprehension mediated by ICT.